1977
DOI: 10.4269/ajtmh.1977.26.248
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Studies in Human Schistosomiasis

Abstract: Complement dependent cytotoxic antibodies for Schistosoma mansoni schistosomules were studied in a Brazilian population. The sera of S. mansoni-infected patients gave a high percentage of cytotoxicity (63.4%) compared with sera from persons not infected (8.7%). The IgG class and the specificity of these cytotoxic antibodies are defined. The index of lethality appeared to be independent of the titers of other specific anti-S. mansoni antibodies. A statistical correlation was found between the index of lethality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This model is consistent with previous observations that show the importance of antibodies and exposing inner parasite tissues for a successful immune response for eliminating schistosomes ( 51 55 ). In vitro studies have shown that the addition of antibodies is necessary for effector cells (e.g., eosinophils) to kill schistosomula ( 51 53 ). Similarly, in vivo, praziquantel-treated adult schistosomes were only killed when immune cells and antibodies gained access to inner parasite tissues through the damaged tegument ( 54 , 55 ).…”
Section: Discussionsupporting
confidence: 93%
“…This model is consistent with previous observations that show the importance of antibodies and exposing inner parasite tissues for a successful immune response for eliminating schistosomes ( 51 55 ). In vitro studies have shown that the addition of antibodies is necessary for effector cells (e.g., eosinophils) to kill schistosomula ( 51 53 ). Similarly, in vivo, praziquantel-treated adult schistosomes were only killed when immune cells and antibodies gained access to inner parasite tissues through the damaged tegument ( 54 , 55 ).…”
Section: Discussionsupporting
confidence: 93%